The Influence of Motivation and Compensation on the Work Ethic of Employees of PT. Agrindo Seluma - Mardiyah Mardiyah; Juliyus Saputra (Journal of Indonesian Management, 2022)
This study aims to determine the effect of motivation and work compensation on the work ethic of employees of PT. Agrindo Seluma either partially or simultaneously. There are several factors that will be discussed in this study, including motivation and compensation. The objects in this study are employees at PT. Agrindo Seluma, totaling 36 people. In this research, the writer uses data collection methods by means of observation, questionnaires or questionnaires and documentation. There are several data analysis techniques used in this study, including using multiple linear regression analysis, determinant coefficients and also hypothesis testing. The results of the study concluded that first, motivation has an effect on the work ethic of employees of PT. Agrido Seluma. The influence given by the motivation variable (X1) on the work ethic of employees (Y) is significant, it can be seen from the tcount value of 2.151 which is greater than ttable 2.005 and the sig value obtained is 0.018 which is smaller than 0.05. Second, compensation has an effect on the work ethic of employees of PT. Agrido Seluma. The effect given by the compensation variable (X2) on the work ethic of employees (Y) is significant, it can be seen from the tcount value of 2,695 which is greater than ttable of 2,005 and the sig value obtained is 0.001 less than 0.05. Third, motivation and compensation have a simultaneous effect on the work ethic of employees of PT. Agrido Seluma. The effect given by the employee benefits variable (X2) on the employee's work ethic (Y) is significant, it can be seen from the tcount 2,695 which is greater than ttable 2,005 and the sig value obtained is 0,001 which is smaller than 0,05.